A world of circuits: the shift from impact to circulation - Beigel, Maria Fernanda (2018)
Accounting for this history of academic domination by the centers, even in the most critical perspectives, has often invisibilized other circuits of recognition that long ago called in question the ?national? and pre-existed the ?mainstream?. Mostly because of the scarce circulation of the empirical studies of peripheral science but also probably due to the limits established by the national perspective, typical of the dominant studies of science. For a long time I have been observing the Latin American academic circuit and the role played by publishing networks and regional institutions that evolved along with national fields in a complex and entangled history. This circuit goes back far ago. It emerged in a 200 year intellectual platform and it was consolidated by the 1960s through regional academic institutions such as CEPAL, CELADE, FLACSO and CLACSO ?this latter playing a central role coordinating initiatives for the visibilization of social research produced in Latin America (Beigel 2003, 2006, 2010). It is a consolidated intellectual space endowed with strong regional traditions. Comparing with Europe, with all the achievements made at the level of economic integration, it has not yet been able to configure itself as an intellectual regional space (Sapiro, 2018). Conversely, Latin America has had difficulties in consolidating its economic integration which only had fragmentary episodes during the XXth century.